Demographic Variables and Internet Shopping in Nigeria - Ifeanyichukwu, Chioma Dili (International Research Journal of Management, IT & Social Sciences, 2016)
The rapid advancement in technology has affected all commercial activities including retailing/shopping, thereby causing a paradigm shift in the way things are done. Internet shopping has become the next big thing in e-business/ e-commerce and is definitely the future of shopping in Nigeria and the world at large. More and more firms /retailers are launching platforms via the internet to facilitate the act of shopping. The knowledge of the demographic characteristics of consumers will to a large extent help these e-retailers in their efforts geared towards consumer satisfaction. However, 311 internet shoppers in Nigeria were randomly selected and used as respondents for the study and structured questionnaire was the major instrument for data collection. The hypotheses generated for the study were tested using crosstab Chi square. Findings revealed a relationship between the demographic variables and internet shopping.